Crime, Bio-Agriculture and the Exploitation of Hunger - Walters, Reece (The British journal of criminology, 2006)
The rapid expansion of biotechnology during the past decade has created widespread debate and concern within the agricultural sector and consumer groups. This article examines the monopolization of bio-technology and the political economy of genetically modified food. It further explores the ways that powerful governments and corporations seek to dominate global food markets whilst exploiting, pressuring and threatening vulnerable countries. In doing so, it provides a detailed examination of Zambia, which has experienced significant political and economic pressure from Western governments and corporations to accept genetically modified maize. Finally, it explores eco-crime' within frameworks of state and corporate crime, international environmental law and emerging discourses in green criminology